Pengembangan Bahan Ajar Matematika Berbasis PMRI Pada Materi Kubus Dan Balok Kelas VIII - Efuansyah, Efuansyah; Wahyuni, Reni (Pendidikan Matematika Universitas PGRI Yogyakarta, 2018)
The purpose of this research is to develop teaching materials use Approach of Indonesian Realistic Mathematics (PMRI) on Cube and cuboid material for grade VIII students of SMP Negeri 13 Lubuklinggau and to know the quality of teaching material is seen from the aspect of validity and practicability. RME or in Indonesia is better known by PMRI is a learning approach mathematics oriented to everyday life close to the world of students, it aims to make it easier for students to understand problems and solve mathematical problems. This research is development research with the development model of ADDIE ( Analysis, Design, Development, Implementation, Evaluation). phase analysis includes student needs analysis and curriculum analysis, the design phase includes the preparation of the map needs of teaching materials, the establishment of teaching materials structure and the making of research instruments. Development phase includes the preparation of teaching materials and validation of teaching materials on the expert, the implementation phase includes teaching experiments on 3 students (one to one), small group (small group) and field test. The evaluation phase includes the assessment of teaching materials by teachers and students. The research used Approach of Indonesian Realistic Mathematics (PMRI) on cube and cuboid material, the result of research showed that (1) the quality of teaching material is seen from aspect of validity and practicality included in criterion either based on four expert lecturer (Expert Content / Mathematics, Media Expert and Expert Language).Keywords: PMRI, Cube, Cuboid, ADDIE